Differences in Hands-off Time According to the Position of a Second Rescuer When Switching Compression in Pre-hospital Cardiopulmonary Resuscitation Provided by Two Bystanders: A Randomized, Controlled, Parallel Study - Kim, Yong Hwan; Lee, Jun Ho; Lee, Dong Woo; Cho, Kwang Won; Kang, Mun Ju; Kim, Yang Weon; Lee, Kyoung Yul; Lee, Young Hwan; Kim, Jin Joo; Hwang, Seong Youn (Journal of Korean medical science, 2015)
The change of compressing personnel will inevitably accompany hands off time when cardiopulmonary resuscitation (CPR) is performed by two or more rescuers. The present study assessed whether changing compression by a second rescuer located on the opposite side (OS) of the first rescuer can reduce hands-off time compared to CPR on the same side (SS) when CPR is performed by two rescuers. The scenario of this randomized, controlled, parallel simulation study was compression-only CPR by two laypersons in a pre-hospital situation. Considering sex ratio, 64 participants were matched up in 32 teams equally divided into two gender groups, i.e. , homogenous or heterogeneous. Each team was finally allocated to one of two study groups according to the position of changing compression (SS or OS). Every team performed chest compression for 8 min and 10 sec, with chest compression changed every 2 min. The primary endpoint was cumulative hands-off time. Cumulative hands-off time of the SS group was about 2 sec longer than the OS group, and was significant (6.6 ± 2.6 sec vs. 4.5 ± 1.5 sec, P = 0.005). The range of hands off time of the SS group was wider than for the OS group. The mean hands-off times of each rescuer turn significantly shortened with increasing number of turns (P = 0.005). A subgroup analysis in which cumulative hands-off time was divided into three subgroups in 5-sec intervals revealed that about 70% of the SS group was included in subgroups with delayed hands-off time ≥ 5 sec, with only 25% of the OS group included in these subgroups (P = 0.033). Changing compression at the OS of each rescuer reduced hands-off time compared to the SS in prehospital hands-only CPR provided by two bystanders.